PANDANGAN PEREMPUAN POLITISI MENGENAI KELUARGA SAKINAH (Studi Terhadap Anggota Dewan Perwakilan Rakyat Daerah (DPRD) Kota Malang) - Erfaniah Zuhriyah, Elmi Farikha, (EGALITA, 2008)
Conventionally, earning money in a family is husbandâ€™s duty and doing chores such as taking care husband and children is wifeâ€™s. However, most women decide to participate in public arena activelyÂ  is a recent phenomenon. As a result, womenâ€™s conventional duty is shifting now. Some women politicians, for example, must manage their time for managing the public affairs and taking care the family. It may cause the family more vulnerable towards conflict and eventually may bring it to the divorce. Therefore, some efforts should be taken to maintain the family. It is also what some women politicians in Malang who sit in the parliament practice to keep their families is still harmonious. They have their own opinion and some tips about â€œestablished familyâ€ (keluarga sakinah) which are influenced by experiences, education, family support, age and the fail of maintaining the family. They are considered to be successfull politicians women in maintaining their public position as well as domestic position to maintain their family.Â  Â Kata kunci: keluarga, sakinah, perempuan, politik.